Study on the Coordinated Development of Urbanization Level and Ecosystem Service Patterns in Xinjiang, China - Ji Rui; Mutalifu Nadiye; Zhang Weijun; Guo Luo (E3S Web of Conferences)
This study investigates the spatiotemporal coordination between urbanization and ecosystem service values (ESV) in Xinjiang, China, from 1990 to 2020. Using multi-source geospatial and socioeconomic data—including land use, GDP, population, and night-time lights—a Coupling Coordination Degree (CCD) model was employed to analyze urban–ecological dynamics. Results show a two-stage urbanization process: steady growth (1990-2005) and rapid expansion (2005-2020), especially in northern cities. Concurrently, ESV declined after 2015 due to water and forest loss from land conversion and climate change. While urbanization and ESV coordination improved until 2015, it deteriorated afterward, signaling increasing ecological stress. The findings highlight the need for integrated urban planning, ecological compensation, and sustainable land-use policies to maintain balance between economic growth and ecosystem preservation in arid regions.